INVESTIGATING THE AWARENESS AMONG POTENTIAL HOMEBUYERS TOWARDS ELEMENTS OF GREEN RESIDENTIAL BUILDING - Mazli, Muhammad Firdaus; Fauzi, Nurul Sahida (PLANNING MALAYSIA, 2022)
The number of green residential buildings in Malaysia is on the rise trend. However, there is an imbalance in the amount of green residential buildings available in main cities. Why do things like this happen? Is there a lower demand for green residential buildings in Malaysia's other main cities? Are potential homebuyers aware of the elements of green residential buildings? Therefore, this research was conducted to identify the demand for green residential building and to investigate potential homebuyers' awareness towards the elements of green residential building. The city of Ipoh, Perak, was chosen as the study's focal point, and Ipoh residents with good professions were chosen as respondents. This is because Ipoh has less green residential buildings than some other cities in Malaysia. A quantitative approach was adopted. A total of 384 responses were accepted for analysis. The collected data were analyzed using frequency analysis and the relative importance index (RII). According to the data, the majority of potential homebuyers in Ipoh, Perak, are aware on the elements of green residential building and are willing to purchase it in the future. This indicates that this residential concept is in high demand in the Ipoh market. Ipoh residents are also well aware of the elements of a green residential building. Hence, developers and the state authority would be able to increase the number of green residential developments in Ipoh.